Leader‐following consensus of uncertain strict feedback multiagent systems subject to sensor and actuator attacks - Gao, Rui; Huang, Jiangshuai (International journal of robust and nonlinear control, 2020)
Summary This article addresses the leader‐follower consensus control of multiple uncertain strict‐feedback nonlinear systems subject to sensor and actuator attacks. The assumption on the simultaneity and uniformity of adversarial attacks in previous literature are no longer needed and a fully distributed adaptive control scheme is proposed, which does not depend on the original state information but on the disrupted state measurement. It is shown that the consensus errors of high‐order uncertain nonlinear multiagent systems are uniformly ultimate bounded in presence of cyberattacks. Finally, the effectiveness of the proposed control scheme is verified by numerical examples.